2018
DOI: 10.18632/oncotarget.24894
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization andin vivopro-tumor properties of a highly conserved matrikine

Abstract: Elastin-derived peptides (EDPs) exert protumor activities by increasing tumor growth, migration and invasion. A number of studies have highlighted the potential of VGVAPG consensus sequence-derived elastin-like polypeptides whose physicochemical properties and biocompatibility are particularly suitable for in vivo applications, such as drug delivery and tissue engineering. However, among the EDPs, the influence of elastin-derived nonapeptides (xGxPGxGxG consensus sequence) remains unknown. Here, we show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…Matrikines like EDPs were shown to promote tumour cell invasion. 4,5,7 The present study provides evidence that EDP treatment of tumour cells induces a switch from a mesenchymal cell phenotype to an amoeboid-like phenotype characterised by a highly dynamic membrane blebbing and by extracellular vesicle shedding. These findings may explain why EDPs favour tumour cell invasion and metastasis.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Matrikines like EDPs were shown to promote tumour cell invasion. 4,5,7 The present study provides evidence that EDP treatment of tumour cells induces a switch from a mesenchymal cell phenotype to an amoeboid-like phenotype characterised by a highly dynamic membrane blebbing and by extracellular vesicle shedding. These findings may explain why EDPs favour tumour cell invasion and metastasis.…”
Section: Discussionmentioning
confidence: 53%
“…Among EDPs, VGVAPG and AGVPGLGVG peptides were reported to stimulate cell invasion. [4][5][6][7] They increase MMP-2, MT1-MMP, uPA and Hsp90 secretion by cancer cells. Hsp90 was shown to interact with many extracellular proteins involved in cancer progression and metastasis and to be of critical importance.…”
Section: Introductionmentioning
confidence: 99%
“…AGVPGLGVG) plays a key role in tumor progression by promoting tumor cell blebbing and extracellular vesicle shedding following its interaction with the ribosomal protein SA (17). The structure of hN5 has been analyzed previously by CD, FT-IR and NMR spectroscopies (16). This report concluded that the structure of the peptide was a mixture of random coils and b-turns.…”
Section: Discussionmentioning
confidence: 95%
“…However, AGVPGLGVG induces angiogenesis, tumor progression, secretion of proteases higher than other EDPs in carcinomas. Moreover, in vitro, it behaves like amyloid-like peptides harboring the XGGXG motif by forming cross b-sheets at the supramolecular level (16). Very recently, Brassart and colleagues have shown that the receptor mediating AGVPGLGVG biological effects, and identified as lactose-insensitive, is the Ribosomal Protein SA (17).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the basement membrane (BM), a specialized extracellular matrix (ECM), has been recognized as a key regulator of cell behavior, and not only as an architectural support. BM is an important structural and functional component of blood vessels (Silva et al, 2018). Several BM components were reported to largely participate in the regulation of tumor angiogenesis (Kalluri, 2003).…”
Section: Introductionmentioning
confidence: 99%